A review of social grade - Higgins, Alisa (Cranfield School of Management, 1980)
The report is the result of an investigation by Cranfield School of Management into the effectiveness of social grade as a determinant of buyer behaviour. A study of usership by social grade of a wide range of products and over 10 years was undertaken, and it was found that while social grade discriminates to some extent for most products,it discriminates less well for many areas than it did ten years ago. The reason for this is not a change in the effectiveness of the measure so much as change in purchasing behaviour. Social grade performs consistenly better for some areas, such as durables, than for others, such as groceries.